PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI BEBAS KELAS VA SD NEGERI BINAAN KHUSUS DUMAI - Darul Fekri Fekri; Hamizi '; Lazim. N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak: This research is motivated by the low skills of writing poetry in even semester 2013/2014. From the preliminary data obtained showed that students who are skilled amounted to 6 people and less skilled students numbered 22 people, with an average value of 53.57. This is because teachers rarely use learning models during the learning process in the classroom. From these problems is necessary to study a class action by applying the Contextual Teaching and Learning model (CTL). This research conducted in SD N Binsus Dumai. the research subjects are students of class V A totaling 28 people, male students 11 and female students 17 people. The research was conducted two cycles. Data collection instruments in this study was the observation sheet teacher activity, student activity observation sheet and daily tests. observation results showed that the activity of teachers and students has increased. Activities teachers in first cycle with a percentage of 75%. Furthermore, in the second cycle to 90% with an increase of 15%. Acceptance of student activity against of Contextual Teaching and Learning models (CTL) in the first cycle with the percentage of 65%. Furthermore, on the second cycle increased to 85% with an increase of 5%. Once applied the Contextual Teaching and Learning model (CTL) in learning, students skilled totaled 9 students, while less skilled students totaled 19 students, with an average value becomes 69.64. In the second cycle there is an increase, evidenced by the results of the second cycle of daily tests show that students who are skilled totaling 25 students. While students who are less skilled totaling 3 students with an average value that is 84.46. Based on these results we concluded that the application of the Contextual Teaching and Learning model (CTL) can increase the writing skill in Free Poetry of Student Class V A SD N Binsus Dumai with satisfactory results. Keywords: Contextual Teaching and Learning (CTL), Free Poetry Writing.